Crystalline assembly of perylene in metal–organic framework thin film: J-aggregate or excimer? Insight into the electronic structure. (16th October 2020) - Kozlowska, Mariana; Pramudya, Yohanes; Jakoby, Marius; Heidrich, Shahriar; Pan, Liuyang; Richards, Bryce S; A Howard, Ian; Wöll, Christof; Haldar, Ritesh; Wenzel, Wolfgang
Abstract: The spatial orientation of chromophores defines the photophysical and optoelectronic properties of a material and serves as the main tunable parameter for tailoring functionality. Controlled assembly for achieving a predefined spatial orientation of chromophores is rather challenging. Metal–organic frameworks (MOFs) are an attractive platform for exploring the virtually unlimited chemical space of organic components and their self-assembly for device optimization. Here, we demonstrate the impact of interchromophore interactions on the photophysical properties of a surface-anchored MOF (SURMOF) based on 3, 9-perylenedicarboxylicacid linkers. We predict the structural assembly of the perylene molecules in the MOF via robust periodic density functional theory calculations and discuss the impact of unit topology and π–π interaction patterns on spectroscopic and semiconducting properties of the MOF films. We explain the dual nature of excited states in the perylene MOF, where strong temperature-modulated excimer emission, enhanced by the formation of perylene J-aggregates, and low stable monomer emission are observed. We use band-like and hopping transport mechanisms to predict semiconducting properties of perylene SURMOF-2 films as a function of inter-linker interactions, demonstrating both p-type and n-type conduction mechanisms. Hole carrier mobility up to 7.34 cm 2 Vs −1 is predicted for the perylene SURMOF-2. The results show a promising pathway towards controlling excimer photophysics in a MOF while controlling charge carrier mobility on the basis of a predictive model.